DIVERSIFIKASI KERIPIK TEMPE PONDOK PESANTREN SIRAJUSSAADAH DEPOK - ilmi, ibnu malkan bakhrul; Sofianita, Nur Intania; Arini, Firlia Ayu; Anwar, Khoirul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2023)
The Sirajussa'adah Islamic Boarding School implements entrepreneurial activities for teenage students studying atthe Islamic boarding school in order to improve the skills of the students and instill an entrepreneurial spirit in theirstudents in carrying out tempe processing business activities called